Psychtech & Health: From Interdisciplinarity to a Transdisciplinary Practice - José Vasconcelos-Raposo (PsychTech & Health Journal)
The scientific journal that we now launch is intended to be a platform for the promotion of interdisciplinary dialogue and, eventually in the long term, the dissemination of the transdisciplinarity that today's real world requires.